NFT 데이터 파일 무결성 검사를 위한 해시알고리즘 활용 - 송효준(Hyojun Song); 정송헌(Songheon Jeong); 김경백(Kyungbaek Kim) (디지털콘텐츠학회논문지, 2023)
Non Fungible Token(NFT) 시장 확대로 여러 NFT 취약점 사례들이 나타나고 있다. NFT의 경우 스마트계약만 블록체인에 저장하고 실제 미디어 데이터는 외부에 저장한다. 이로 인해 블록체인의 중요한 기능인 무결성이 외부 미디어 데이터에 적용되지 않는다. 외부 저장소로 InterPlanetary File System(IPFS)를 사용하지만, 데이터를 불러올 때 적절한 파일이 없거나 잘못된 파일을 불러오는 경우가 있다. 발급된 NFT가 가리키는 미디어 데이터 주소가 공격자에 의해 변조될 여지가 있다. 이에 해시 알고리즘을 사용하여 무결성을 보장하고 파일 위변조를 감지하는 방안을 제시한다. 해시 알고리즘을 이용해 미디어 데이터 정보를 스마트계약에 저장함으로써 해시값의 무결성을 보장한다. 사용자가 데이터를 불러올 때 무결성을 다시 확인한다. 이 방식은 비용 효과적으로 미디어 데이터의 무결성과 진위를 검증할 수 있게 한다. As the Non Fungible Token(NFT) market expands, several cases of NFT vulnerabilities are appearing. In the case of NFT, only the smart contract is stored on the blockchain, and the actual media data are stored externally. This prevents integrity, an important feature of blockchain, from being applied to external media data. InterPlanetary File System(IPFS) is used as an external storage, but there are cases where there is no appropriate file or the wrong file is loaded when loading data. There is room for an attacker to tamper with the media data address indicated by the issued NFT. Therefore, we propose a method that uses a hash algorithm to ensure integrity and detect file forgery. The integrity of the hash value is guaranteed by storing media data information in a smart contract using a hash algorithm. Integrity is re-checked when the user retrieves data. This method makes it possible to verify the integrity and authenticity of media data in a cost-effective way. KCI Citation Count: 1